Evaluation of burnout among Board-Certified Psychiatric Pharmacists in the United States - Samantha Catanzano, PharmD, BCPP; Jennifer N. Gemmellaro, PharmD, BCPP, BCPS; Melissa Mooers Gross, BS, PharmD, MHA, BCPP, BCPS, BCGP, BCIDP, CPEL, CPPS; Monica Fahmy, PharmD, BCPP, BCPS; Gregory H. Payne, MBA, CAE; Kelly C. Lee, PharmD, MAS, BCPP, FCCP (Mental Health Clinician)
Introduction Burnout is an occupational phenomenon resulting from chronic workplace stress that is unsuccessfully managed. Data related to burnout among clinical pharmacists are limited. This study aimed to measure burnout among Board-Certified Psychiatric Pharmacists (BCPPs) and evaluate the correlation between practice characteristics and demographics. Methods This was a cross-sectional survey study of BCPPs. The survey included demographic, practice-related, and burnout questions. The primary outcome was burnout scores using the Maslach Burnout Inventory Human Services Survey for Medical Personnel (MBI-HSS [MP]). Secondary outcomes assessed the practice and demographic factors that may have affected burnout levels. Correlation and regression statistics between MBI-HSS (MP) and practice and demographic variables were performed. Results Of 571 invitees, 225 participated in the study, and 173 respondents were included. Burnout subscale scores were not significantly different based on age, race, gender, marital, or caregiver status; however, a sense of belonging positively influenced all subscale scores. Regular mentorship and engaging in a hobby were correlated with significantly lower emotional exhaustion scores (20.2 vs 24.8, P = 0.028, and 22.7 vs 28.4, P = 0.010). Burnout subscale scores were comparable between practice settings. However, personal accomplishment subscale scores were significantly lower for pharmacists in the inpatient versus outpatient setting (37.1 vs 38.9, P = 0.036). Conclusion BCPPs are at risk for burnout. Race, gender, and patient volume were not associated with burnout. Factors including mentorship, engaging in hobbies, and a sense of belonging were identified as potential modifiers of burnout in BCPPs.